The current phenomenon of Ar-Rahn and Wadi'ah - Hayati, Keumala; Asmuni, Asmuni; Anggraini, Tuti (Accounting and Business Journal, 2023)
This study aims to obtain field results regarding the tendency of public interest in sharia and conventional pawning, which, as we know, conventional pawning provides quite high interest. Today, technological developments are increasing rapidly in line with the business world. The Covid 19 storm resulted in chaos in the business supply chain which had an indirect impact on people's businesses and income. During a pandemic, the percentage of people setting aside their income to save or invest decreased. The performance of pawnshops which continued to grow during the pandemic gave the fact that many people needed fresh funds to continue their lives or to do business. The presence of private pawnshops in the city of Medan cannot be underestimated. OJK noted that there was an increase in the management of pawning permits from 46 pawn businesses. This proves the existence of a pawn business and the benefits it provides to the community. The method used in this study is qualitative research to understand human or social phenomena and supported by literature. The results of this study are that people prefer pawnshops that are always there during an emergency, even if it's a private pawnshop that pays high interest and violates Islamic law